ANALISIS KUALITAS WEBSITE AKADEMIK MENGGUNAKAN METODE WEBQUAL 4.0 DAN IMPORTANCE-PERFORMANCE ANALYSIS (IPA) (Studi Kasus: STIKOM YOS SUDARSO - Alfonsus Simbolon; Muhamad Azrino Gustalika; Yohani Setiya Rafika Nur (STEKOM PRESS, 2023)
Websites have an important role in academic management and enhance the reputation of a company or institution. Website service quality is an important factor in education. On university web ranking sites such as webometrics, Indonesia's ranking is relatively low, including universities in Central Java which are ranked in the 1000's. Therefore, this study aims to find the causative factors and analyze the current quality of academic websites. The Webqual 4.0 method was used in this study to evaluate the quality of websites based on indicators of usability, reliability, novelty and user satisfaction. Importance-Performance Analysis (IPA) is also used to determine indicators that need to be repaired, updated, and maintained based on user perceptions and expectations. This research involved 144 respondents, namely students and staff at STIKOM Yos Sudarso. The results of the study show several indicators that need to be improved on the STIKOM Yos Sudarso website, especially in terms of appearance and quality of information such as novelty and clarity of content. Recommendations from this study include improving the appearance by developing designs and simplifying features. In addition, it is necessary to improve the quality of information by updating information in a timely, accurate and regular manner. Interaction with users also needs to be improved by adding a live chat feature and improving all indicators to build a good website reputation